2003
DOI: 10.1038/sj.ijir.3901026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PDE5 inhibition combined with free oxygen radical scavenger therapy on erectile function in a diabetic animal model

Abstract: Phosphodiesterase (PDE) inhibitors represent an important advance in the treatment of erectile dysfunction (ED). In spite of widespread use and generally good efficacy, as a class they remain ineffective in 15-57% of men. Specific cohorts of patients with severe vascular or neurogenic basis to their ED, such as diabetic men or those who have undergone radical pelvic surgery, demonstrate lower response rates with PDE inhibition treatment. We believe that circulating levels of nitric oxide (NO) may be enhanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 47 publications
4
52
2
2
Order By: Relevance
“…Indeed, a dose-response study in rats showed that 5 mg/kg per day i.p. was the optimal erectogenic dose of sildenafil (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a dose-response study in rats showed that 5 mg/kg per day i.p. was the optimal erectogenic dose of sildenafil (34).…”
Section: Resultsmentioning
confidence: 99%
“…The use of sildenafil is particularly appealing because this drug has been thoroughly studied in terms of its pharmacological effectiveness and safety (34,47). At least 21 genes encode PDE proteins in mammals, each containing several distinct transcriptional units, bringing the number of PDE proteins to Ͼ50.…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy of sildenafil in general population has been reported as 74 --97%, it is only 50 --56% among diabetic individuals. 7,8 As mentioned before, the effect of both AGE inhibitors and cross-link breakers has already been shown in various experimental studies. 4 --6 On the other hand, the potential impact of combining AGE cross-link breaker namely ALT-711 and sildenafil to treat diabetes-related ED remains to be determined.…”
Section: Introductionmentioning
confidence: 82%
“…The authors concluded that vitamin E enhanced the therapeutic effect of sildenafil, which indicated a potential means of salvaging erectile function among men who are refractory to sildenafil. 8 Similarly, Bivalacqua et al 12 reported the effect of combination of sildenafil and NO synthase gene therapy on erectile function in STZ diabetic rats. The authors clearly showed that overexpression of eNOS and cGMP in combination with sildenafil significantly increased both the ICP and total ICP to CNS in the STZ diabetic rats, which was similar to the response observed in control rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation